2010
DOI: 10.1111/j.1365-277x.2010.01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of home enteral feed preparation for children with inherited metabolic disorders

Abstract: Background:  Many children with rare chronic disorders require home enteral tube feeds (HETF) consisting of multiple modular ingredients. Feeds are often complex and the risk of errors during their preparation is high. The consequences of over‐ or under‐concentration can be critical. The aim of the present prospective observation study was to assess the accuracy, skills and technique of caregivers when preparing and administering HETF. Methods:  Fifty‐two HETF patients (median age 7.5 years, range 0.7–18.0 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
0
13
0
2
Order By: Relevance
“…Enteral feed composition is usually complex, requiring an individualized protein and energy profile commonly consisting of separate (or combined) modules of sources of protein, fat, carbohydrate, vitamins and minerals. It is essential that all caregivers administering enteral feeding receive professional instruction in safe feed production and that their feed preparation technique is reviewed on an annual basis [136,172-174]. …”
Section: Methodology and Objectivesmentioning
confidence: 99%
“…Enteral feed composition is usually complex, requiring an individualized protein and energy profile commonly consisting of separate (or combined) modules of sources of protein, fat, carbohydrate, vitamins and minerals. It is essential that all caregivers administering enteral feeding receive professional instruction in safe feed production and that their feed preparation technique is reviewed on an annual basis [136,172-174]. …”
Section: Methodology and Objectivesmentioning
confidence: 99%
“…Previous studies have demonstrated that knowledge and skills in the home environment post‐hospital discharge are less than ideal and may impact on patient safety (Evans et al. , 2006, 2007, 2010, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that in specialist modular feeds for IMD, increasing number of feed ingredients is associated with greater error and inaccurate feed preparation is common [1], [2], [3], [4]. Inaccurate feed production may be associated with feed intolerance, diarrhoea, hypernatraemia, and uneven intake of prescribed nutrients such as protein or fat and even metabolic decompensation [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%